Study of Probiotic Properties and Functional Activities of Yeasts Isolated for Feed Supplement - Niwasabutra, Kanidta; Chaiyawan, Neungnut; Nualsri, Nattharika; Kengkwasingh, Pattarawadee; Nuankham, Kamonsri; Sitdhipol, Jaruwan; Lorliam, Wanlapa; Kingkaew, Engkarat (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2024)
Eighteen isolated yeasts from rice and natural sources are characterized as probiotics. All strains, at 37°C, lack hemolysis and withstand simulated gastrointestinal conditions and bile salts. Strains were identified as Meyerozyma caribbica, Saccharomyces cerevisiae, Pichia kudriavzevii, Starmerella sorbosivorans, Kodamaea ohmeri, Ambrosiozyma kamigamensis, and Metschnikowia koreensis. Strong adherence to intestinal cells was noted, plus sensitivity to certain antifungals, confirming safety. Notably, M. caribbica TISTR 6026 and M. koreensis TISTR 6044 demonstrated xylanase activity. Also, M. caribbica TISTR 6017, S. cerevisiae TISTR 5104, TISTR 5328, and P. kudriavzevii TISTR 6028 exhibited antimicrobial action against pathogens. These four strains showed immunomodulatory potential, impacting phagocytosis, nitric oxide, TNF-α, and IL-6. These findings underscore their promise as versatile probiotics for immunomodulation and addressing pathogens, showcasing their broad potential.